'Our legal responsibility…to intervene on behalf of the child': Recognising public responsibilities for the medical treatment of children. (March 2021) - Bridgeman, Jo
This article argues for recognition of public responsibilities to protect the welfare of children with respect to decisions affecting their health and medical treatment. As the quote in the title of this article, from David Plank, the Director of Social Services responsible for bringing the case of Baby Alexandra before the courts, identifies, early cases concerning children's medical treatment were brought by local authorities to determine responsibilities to protect the welfare of children. In cases such as Re B (1981), Re J (1990) and Re W (1992), the court was asked not only to determine the child's best interests but also to clarify the duties of the local authority, Trust, court and child's parents to the child. The respective duties established apply to all involved in cases brought before the courts on the question of a child's future medical treatment, whether or not the child is in the care of the state. Recent cases concerning the medical treatment of seriously ill children have involved claims of parental authority to determine the care of their child. To the contrary, this article argues that court involvement is required when parents are disagreed with the child's treating doctors over the child's medical treatment because of public as well as parental and professional responsibilities for the welfare of all children.